Evaluasi Ketepatan Pemberian Air Menggunakan Sistem Manajemen Operasi Irigasi (SMOI) di Daerah Irigasi Bondoyudo - Dadan Rahmandani; Eko Winar Irianto; Hanhan Ahmad Sofiyuddin; Susi Hidayah; Iwan Hadihardaja; Edy Anto Soentoro (Jurnal Irigasi, 2017)
Irrigation Operation Management System (SMOI) is an irrigation reporting information system designed to automate data transfer and form reporting by utilizing the internet network. SMOI can shorten the time of reporting and facilitate the evaluation of historical data in support of decision making in an Irrigation Area. Nevertheless, this technology has not been tested on field-scale applications especially in multiple districts irrigation area. The study aimed to analyze the accuracy of SMOI calculations and the correctness of water delivery as the impact of the SMOI application. The research was conducted on the application of SMOI in Bondoyudo Irrigation Area, East Java. The analysis of the calculation accuracy is done by verifying and validating the results of SMOI calculation compared to the calculation of manual form. Analysis of water delivery accuracy is done through water balance simulation based on data in Cropping Season I and II year 2016/2017. Based on the result, the calculation workflow, data retrieval, and flow of data distribution among forms on SMOI in accordance with the provisions in PUPR 12/PRT/M/2015. The simulation results show that SMOI can improve the accuracy of water delivery to the predicted value by 40.7% in Cropping Season I and 21.8% in Cropping Season II. However, when compared with actual irrigation water needs, SMOI has not significally to improved water delivery accuracy. This is due to the calculation of water requirements in manual form and SMOI not yet accommodating the variability of actual climatological conditions.